A Case Series of Acquired Drug Resistance-Associated Mutations in Human Immunodeficiency Virus-Infected Children: An Emerging Public Health Concern in Rural Africa. (17th December 2015) - Gamell, Anna; Muri, Lukas; Ntamatungiro, Alex; Nyogea, Daniel; Luwanda, Lameck B.; Hatz, Christoph; Battegay, Manuel; Felger, Ingrid; Tanner, Marcel; Klimkait, Thomas; Letang, Emilio
Abstract: The acquisition of drug-resistance mutations among African children living with in human immunodeficiency virus on antiretroviral treatment has been scarcely reported. This threatens the overall success of antiretroviral programs and the clinical outcomes of children in care. We present a well characterized series of children from rural Tanzania with acquired drug-resistance mutations to contribute to the better understanding of this emerging public health concern.